Pandangan Kritis terhadap Pendekatan Feminis - Ahmad Adnan (STID DI AL-HIKMAH, 2016)
Indeed, the mission of man on earth is not just worship. But there are other missions into the principles and values ??of the mission on this earth. It begins with a noble task as a manager and developer of this earth that are beneficial to humans and as a means of worship. This is called the prosperity of the earth. Leadership is: the ability to manage, organize, memenaj, regulate, administer, build, guide, and provide tranquility, peace, and security and guarantees to institutions that are under the authority consisting of a group of people, territorial and all of its assets. He is a gift and a burden of responsibility from God for His servants, especially a human, he is a caliph, manager, and leader as verses in discussion-discussion beforehand. Leadership is a responsibility that must be carried out jointly between men and women.